Beheld : a novel - Nesbit, TaraShea (Bloomsbury Publishing, 2020)
Ten years after the Mayflower pilgrims arrived on rocky, unfamiliar soil, Plymouth is not the land its residents had imagined. Seemingly established on a dream of religious freedom, in reality the town is led by fervent puritans who prohibit the residents from living, trading, and worshipping as they choose. By the time an unfamiliar ship, bearing new colonists, appears on the horizon one summer morning, Anglican outsiders have had enough.